Hubungan Beban Kerja, Stres Kerja, Kompensasi, Kepuasan Kerja, Lingkungan Kerja dengan Turnover intention pada Perusahaan Gudang Penyimpanan Barang - Framudita, Sinta; Sumastuti , Efriyani; Akbar , Shofif S (Lembaga Pengembangan Kinerja Dosen, 2025)
This study explores key antecedents of turnover intention among employees in the warehouse industry, with a focus on workload, work stress, and job satisfaction. Conducted at CV. Sejati Pati, the research involved 102 respondents selected using a saturated sampling technique. The study applied a quantitative approach, using a structured questionnaire with a five-point Likert scale. Data were analyzed through multiple linear regression using IBM SPSS 27, including classical assumption tests such as normality, multicollinearity, and heteroscedasticity. The results showed that workload and work stress have a positive and significant effect on turnover intention, while job satisfaction has a negative and significant effect. In contrast, compensation and work environment were found to be statistically insignificant. Simultaneously, all variables jointly contribute to explaining 64.9% of the variation in turnover intention. These findings underscore the critical role of managing job demands and psychological pressure while enhancing employee satisfaction to reduce the likelihood of resignation. The research provides empirical insights for human resource management in high-pressure sectors, particularly warehouses, where operational continuity and labor stability are crucial. It also offers practical implications for developing targeted strategies to improve employee retention and foster a more resilient workforce in logistics operations.